2012
DOI: 10.4102/jamba.v4i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Flooding, flood risks and coping strategies in urban informal residential areas: The case of Keko Machungwa, Dar es Salaam, Tanzania

Abstract: This article presents findings from a study carried out in Keko Machungwa informal settlement in Dar es Salaam under the auspices of the Disaster Management Training Centre of Ardhi University, Tanzania. The settlement has experienced frequent flooding in the past five years, and this study explores the causes, risks, extent of flooding and coping strategies of residents as well as municipality and city officials. Key methods employed in capturing empirical evidence included mapping of zones by severity of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Chatterjee (2010), Sakigele et al (2012) and Ngie (2012) have shown the difficulties, limitations and practical inefficacy of informal settlement dwellers' coping mechanisms against flooding and structural stormwater management strategies.…”
Section: Community-initiated Developmental Moves In Slovo Parkmentioning
confidence: 98%
See 1 more Smart Citation
“…Chatterjee (2010), Sakigele et al (2012) and Ngie (2012) have shown the difficulties, limitations and practical inefficacy of informal settlement dwellers' coping mechanisms against flooding and structural stormwater management strategies.…”
Section: Community-initiated Developmental Moves In Slovo Parkmentioning
confidence: 98%
“…Coping strategies for stormwater against flooding often fall into structural (physical systems, devices and engineered) measures and non-structural measures, as identified by Chatterjee (2010) and Sakigele et al (2012) in Mumbai and Dar es Salaam settlements, respectively. On another scale, the Orangi Pilot Project in Karachi, shows informal settlements' community-wide efforts to fund, manage and maintain their own drainage (and general infrastructural) systems (Hasan, 2008).…”
Section: Infrastructural Inadequacy In Informal Settlements: State 'Fmentioning
confidence: 99%